ChemInform Abstract: The Nanoparticle Biomolecule Corona: Lessons Learned — Challenge Accepted?. Issue 42 (October 2015) - Docter, D.; Westmeier, D.; Markiewicz, M.; Stolte, S.; Knauer, S. K.; Stauber, R. H.
Abstract Review: 221 refs.